Modelling And Simulation Of Overtaking Collision Reduction Systems - Tadesse Negesse (ASTU, 2024)
One Of The Biggest Issues With Two-Lane Highway Traffic Safety Is Passing Collisions. When A Driver Fails To Accurately Analyze The Situation, Collisions Like This Happen. The Framework Model For A Overtaking Collision Reduction System (Ocrs), Which Lowers The Possibility Of Human Error And Helps Drivers Avoid Passing Crashes On Two-Lane Highways, Is Provided In This Study. The Technology Makes Use Of Sensors To Determine The Kind Of Vehicle Obstructing Traffic And To FindV ehicles That Are Approaching From The Oncoming Lane. The Goals Of This Research Are To Create Driving Simulator Trials To Gather Data For Passing Parameter Calculations; And Create The Ocrs Algorithm, Which Detects Trucks (Impeding Vehicles) Based On Signals From Camera And Radar Sensors. Then To Create A Driver Handling Model That Explains Scenarios Where Lane Changes And Maneuver Interruptions Require Throttle Linkage Action And, Finally To Create Algorithm For Proteus And Matlab Simulation. The Purpose Of The Simulation Series Was To Validate The Ocrs Algorithm's Efficacy. In This Study, The Impact Of Driver Behavior On Passing Maneuvers Was Examined, And Algorithms For A Pcws That Helps Drivers Choose Appropriate Passing Spacing During Passing Movements Were Developed. Several Methods, Including Imitation And Mathematical Models, Were Improved To Simulate Real-World Driving Conditions In Simulink. The Proposed Ocrs Uses A Radar Sensor Placed In The Passing Vehicle To Detect Opposing Vehicles Travelling In The Left Lane And Calculate Their Relative Distance And Speed In Order To Estimate The Time To Collision. Then Based On The Position And Relative Speed Of Oncoming Vehicle The Rear Leading Vehicle Lcd Display Safe To Overtake Or Not Safe To Overtake Based On Sensor Data. Then The Following Vehicle Will Take Text And Color Of Lcd Display Of Rear Of Leading Vehicle To Actuate For Engaging Or Disengaging The Acceleration Pedal Wire From Throttle Valve By Model Of Throttle Linkage. Therefore, The Input From Radar Sensor And Algorithms Will Be Governing Display Of The Leading Vehicle. Again The Leading Vehicle Display Will Govern The Throttle Linkage Actuator.
Keywords: Advanced driver assistance system, overtaking assistant system, Fuzzy logic, overtaking decision making. OAS, Vehicle to Vehicle communication, collision avoidance, Microcontroller, arduino, Proteus